Rat-ical justice: Care at the interface of the human and the nonhuman - Davis, Delaney; Säfdal, Lisa (My University, 2024)
Coincident with the development of human civilization was the emergence of a new type of critter: one not domesticated, not beloved, but similar to us in so many aspects that they abound in our environments— the urban rat. This urban critter burgeons in numbers that we humans find threatening if not overtly problematic. Ironically, this “problem” is one of our own creation; our actions are what have allowed these critters to thrive. But instead of assuming responsibility for inviting them to the table, we blame them for arriving at our doorstep and then poison their dinner. Using the widespread mistreatment of rats as an example, this thesis critiques the anthropocentric worldview that enables the abuse of marginalized individuals and absolves us of accountability for our actions. It argues that a fundamental shift away from this worldview is necessary in relearning how to exist in a world of others. It also aims to propose ways to initiate this shift toward respectful cohabitation through the exploration of various social and spatial facilitators. By utilizing four tactics—strategic anthropomorphism, public engagement, the mapping of heterotopias, and negotiation—this work explores how practices of care can showcase the perspectives of neglected nonhumans and facilitate respectful cohabitation between rats and humans in an urban environment. The outcome of this thesis is a series of experiments that address various aspects of our relationship with urban rats. Key findings include a collection of strategies for learning how to foster empathy for rats, efforts aimed at advocating for their rights as urban inhabitants, and the showcasing of the homes they make in our cities’ in-between spaces. Furthermore, this thesis results in experimental negotiations that imagine spaces that compromise rather than utilize traditional means of control to enable respectful cohabitation in the urban landscape. Rat-ical Justice shows that empathy and care can, and indeed should, be extended to every individual, human or nonhuman
Keywords: rats, critical posthumanism, care, cohabitation, nonhuman rights